2009
DOI: 10.1002/cmdc.200900258
|View full text |Cite
|
Sign up to set email alerts
|

4,4‐Dimethyl‐ and Diastereomeric 4‐Hydroxy‐4‐methyl‐ (2S)‐Glutamate Analogues Display Distinct Pharmacological Profiles at Ionotropic Glutamate Receptors and Excitatory Amino Acid Transporters

Abstract: Subtype-selective ligands are of great interest to the scientific community, as they provide a tool for investigating the function of one receptor or transporter subtype when functioning in its native environment. Several 4-substituted (S)-glutamate (Glu) analogues were synthesized, and altogether this approach has provided important insight into the structure-activity relationships (SAR) for ionotropic and metabotropic glutamate receptors (iGluRs and mGluRs), as well as the excitatory amino acid transporters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…From these experiments, compound 4 showed selectivity for EAAT2 over EAAT1 and EAAT3 (IC 50 of 24 μM at EAAT2). A comparison to previously reported EAAT inhibitory profiles from a large number of L-2,4-syn-Glu analogues (analogues of derivative 3) suggested that the observed preference for EAAT2 is a characteristic of this class of compounds, although the structural basis for the trend was not yet described [93].…”
Section: Othersmentioning
confidence: 99%
“…From these experiments, compound 4 showed selectivity for EAAT2 over EAAT1 and EAAT3 (IC 50 of 24 μM at EAAT2). A comparison to previously reported EAAT inhibitory profiles from a large number of L-2,4-syn-Glu analogues (analogues of derivative 3) suggested that the observed preference for EAAT2 is a characteristic of this class of compounds, although the structural basis for the trend was not yet described [93].…”
Section: Othersmentioning
confidence: 99%
“…While the key residues involved in kainic acid recognition are highly conserved, a few mutated residues create subtle geometry and cavity differences. , These mutations are likely the reason for the classification of GluK subtypes into low affinity for kainic acid (GluK1–3) or high affinity (GluK4–5) (Table S5, Supporting Information) . In fact, the glutamate-binding pocket volume was found to decrease in the order GluK1 > GluK3 > GluK2. , These differences have been exploited in the design of glutamate-derived ligands to achieve GluK1-selective agonists and antagonists. …”
Section: Protein–ligand Interaction: the Binding Site Of Kainic Acidmentioning
confidence: 99%
“…12 Furthermore, GluK antagonists might have a beneficial effect on neurodegenerative diseases such as multiple sclerosis, 13 Alzheimer's disease, 14 and Huntington's disease, 15 as well as in several psychiatric disorders including schizophrenia, 16 major depression, 17 autism, 18 bipolar disorder, 19 and obsessive-compulsive disorder. 20 In the search for subtype selective ligands for iGluRs, a substantial number of Glu analogues have been prepared and characterized pharmacologically, including >200 different 4substituted Glu analogues by us [37][38][39][40][41][42] and others 35,[43][44][45][46][47] (see Table 1). Also a number of analogues of the natural product KA have been prepared, including the structurally simplified KA analogue 3a (CPAA) as well as the conformationally restricted analogues 1b 27 and 1c 23 (Table 1).…”
Section: Introductionmentioning
confidence: 99%